Levantamento de indicadores de qualidade do solo como base para a construção de um índice de sustentabilidade agrícola - FEITOSA , Ana Luiza Privado Martins (2019)
Soil attributes can be modified because management practices and crops, changing edaphic quality and negatively affecting the sustainability of agricultural activity. Since the concept of quality is subjective, the construction of quantitative assessment systems based on indicators is very important. This work is based on the hypothesis that it is possible to select soil quality indicators under different fertilization regimes, as a basis for the elaboration of an agricultural sustainability index. The present study aimed to propose soil quality indicators under different fertilization regimes to compose an Agricultural Sustainability Index (ASI). The experimental area is located in the municipality of Brejo, state of Maranhão, Brazil. Two experiments were carried out with alley crop using legume, of which the pruning was used in the treatments with legume. One of experiments corresponded to Leucena (Leucaena leucocephala), and the other to Gliricidia (Gliricidia sepium). The area between the legume lines was divided into plots in a randomized block design. The area with Leucaena was divided in 24 plots, with 4 replicates and 6 treatments, which were nitrogen (N), leucaena (L), nitrogen + leucaena (N + L); humic acid + leucaena (HA + L); humic acid + nitrogen (HA + N) and humic acid + nitrogen + leucaena (HA + N + L). The area with Gliricidia was divided into 32 plots with 4 replicates and 8 treatments, which were potassium (K), gliricidia (G), humic acid (HA), humic acid + potassium (HA + K), potassium (K + G), humic acid + gliricidia (HA + G), humic acid + potassium + gliricidia (HA + K + G) and uncovered soil (US). Each plot was cultivated with maize (Zea mays L.) to obtain grains yield. Biological and chemical attributes were used in this research. Soil fauna was used as biological indicator and was collected through pitfall traps. The total abundance, dominance, richness, Shannon-Wiener diversity index and Pielou equitability index of edaphic fauna were determined. Soil samples were collected at depths of 0–5 cm, 5–10 cm and 10–20 cm to obtain chemical data. Potential acidity, pH, soil organic carbon (SOC), available phosphorus, exchangeable potassium, calcium and magnesium, cation exchange capacity (CEC), sum of base cation (SBC) and base saturation (BS) were determined. Principal component analyzes (PCA) were performed to correlate soil biological and chemical attributes with maize grains yield. An ASI was suggested based on the indicators used in this study, whose weights were obtained on the PCAs results. This research indicates that biological and chemical attributes of soil quality are sensitive to changes in soil fertilization regimes and that these attributes can be associated with maize grains yield and can be used as indicators of soil quality in the composition of an Agricultural Sustainability Index.